2017
DOI: 10.1021/acs.nanolett.7b00425
|View full text |Cite
|
Sign up to set email alerts
|

Room-Temperature Quantum Ballistic Transport in Monolithic Ultrascaled Al–Ge–Al Nanowire Heterostructures

Abstract: Conductance quantization at room temperature is a key requirement for the utilizing of ballistic transport for, e.g., high-performance, low-power dissipating transistors operating at the upper limit of “on”-state conductance or multivalued logic gates. So far, studying conductance quantization has been restricted to high-mobility materials at ultralow temperatures and requires sophisticated nanostructure formation techniques and precise lithography for contact formation. Utilizing a thermally induced exchange … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
44
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 49 publications
2
44
0
1
Order By: Relevance
“…The most relevant are changes in the configuration of electronic states due to quantum confinement that can give place to more exotic electronic effects such as localization and splitting of the electronic bands. This, in turn, can result in semimetal-semiconductor transitions 243 , or ballistic transport in 1D metallic nanowires 244,245 , among other phenomena. Also, due to the low dimensionality, there is a higher surface to volume ratio, which reverts in a significant presence of surface conduction or surface effects, characteristic of nanowires.…”
Section: Template Assisted Fabrication Of Inorganic Structuresmentioning
confidence: 99%
“…The most relevant are changes in the configuration of electronic states due to quantum confinement that can give place to more exotic electronic effects such as localization and splitting of the electronic bands. This, in turn, can result in semimetal-semiconductor transitions 243 , or ballistic transport in 1D metallic nanowires 244,245 , among other phenomena. Also, due to the low dimensionality, there is a higher surface to volume ratio, which reverts in a significant presence of surface conduction or surface effects, characteristic of nanowires.…”
Section: Template Assisted Fabrication Of Inorganic Structuresmentioning
confidence: 99%
“…With respect to the scalability of the NDR in Ge, we found that heterostructure devices with Ge channel lengths L Ge < 100 nm showed no signs of NDR, which we attribute to the quasi‐ballistic [ 43 ] nature of such short channel Ge heterostructure devices. Consequently, the best performing devices were found to have d NW = 20 nm and L Ge = 150 nm just over three times longer than the scattering mean free path in our Ge NWs.…”
Section: Resultsmentioning
confidence: 97%
“…Consequently, the best performing devices were found to have d NW = 20 nm and L Ge = 150 nm just over three times longer than the scattering mean free path in our Ge NWs. [ 43 ] Compared to state of the art NDR devices, our architecture exhibits an ultra‐short footprint. As shown in Figure a, embedded in the proposed top‐gate architecture, these devices can be operated with V Peak = 0.9 V and V Valley = 1.2 V, still providing a PVR of 4.5 at T = 295 K. As shown in Figure 4b,c respectively, a longer Ge channel increases the device resistance, shifting V Peak and V Valley to higher voltages.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…8,[14][15][16] Here, we extend the method to extract the thermal conductivity of a thermoelectric material and the metal leads, the thermal interfaces to a substrate, and the Peltier coefficient from the observation of the temperature fields. The nanowire device consists of a germanium (Ge) segment which is monolithically integrated in a single crystalline aluminium (c-Al) nanowire with atomically sharp interfaces 17 and a diameter of 35 nm. A dark field scanning transmission electron microscope (DF-STEM) image of the nanowire cross-section, a SEM image and a sketch of the device are shown in Fig.…”
mentioning
confidence: 99%